2021
DOI: 10.24093/awej/vol12no3.16
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Azerbaijani Students’ Intercultural Competence through Distance Education of Foreign Languages

Abstract: The main aim of this study is to determine the advantages and disadvantages of distance teaching and promoting Intercultural Competence in learning foreign languages in the Azerbaijani higher education system. Nowadays the growing tendency of remote education proves that, education has become more reachable in comparison to the past decades. At the same time, distance education has brought new demands and regulations to the education system. The COVID-19outbreak has necessitated the online teaching process res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Research on innovative foreign language learning strategies has revealed a number of positive strategies, so such strategies can be used by weaker students who are trying to improve their learning. A foreign language teacher with the goal of teaching his students how to use language learning strategies should learn more about the students, their interests, motivations, and learning styles (Imanova, 2021). He or she can examine the foreign language learning strategies that students have chosen and use by observing their behavior in class (Doghonadze, Aliyev, Halawachy, Knodel & Adedoyin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research on innovative foreign language learning strategies has revealed a number of positive strategies, so such strategies can be used by weaker students who are trying to improve their learning. A foreign language teacher with the goal of teaching his students how to use language learning strategies should learn more about the students, their interests, motivations, and learning styles (Imanova, 2021). He or she can examine the foreign language learning strategies that students have chosen and use by observing their behavior in class (Doghonadze, Aliyev, Halawachy, Knodel & Adedoyin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Its goal was to evaluate how Algerian EFL teachers perceived the concepts of culture and intercultural competence in ELT contexts. Imanova (2021) studied the advantages and disadvantages of promoting intercultural competence in foreign language learning. This study specifically focused on learning a foreign language through distance education within the context of higher education in Azerbaijan.…”
Section: Intercultural Competence and Educationmentioning
confidence: 99%
“…In building an educational program, each higher education institution is based on achieving the main goal -training highly qualified personnel who can create competitive products. Education always responds to the changing economy and market demands to train relevant specialists (Imanova, 2021). In such conditions, teachers should not just provide basic professional knowledge.…”
Section: Introductionmentioning
confidence: 99%